THE PALAEOPROTEROZOIC KOMATIITE-PICRITE ASSOCIATION OF FINNISH LAPLAND - Hanski E.; Rastas P.; Huhma H.; Kamenetsky V.S. (My University, 2001)
The large range of chemical variation within intimately associated highly magnesian volcanic rocks in the Palaeoproterozoic Central Lapland Greenstone Belt prompted the construction of a new classification scheme for MgO-rich volcanic rocks, based on an [Al 2 O 3 ] vs [TiO 2 ] diagram where the axes are the Al 2 O 3 and TiO 2 contents (in mole proportions) of the rocks projected from the olivine composition. This diagram places the Lapland rocks in the fields of Ti-enriched komatiites and picrites. Komatiitic rocks are depleted in both light and heavy rare earth elements (LREE and HREE) relative to middle REE (MREE) and possess relatively high TiO 2 even in the most LREE-depleted varieties, whereas picritic rocks approach geochemically Hawaiian picrites. Seven clinopyroxene and whole-rock pairs analysed for Sm–Nd isotopes yield an average age of 2056 ± 25 Ma for the komatiites. Uncontaminated komatiites and picrites have similar positive εNd values (+4) indicating generation from a mantle source with a long-term depletion in LREE relative to MREE. Geochemical characteristics of the komatiite–picrite association, including REE and Nb/Y–Zr/Y systematics, indicate chemical heterogeneities in the source region, which seem to have been created by complex depletion and enrichment processes shortly before or related to a dynamic melting process. The high MgO contents of the rocks coupled with chemical similarity between the Lapland and Hawaiian picrites supports a mantle plume model for their genesis. Nevertheless, the geotectonic evolution appears to have proceeded without significant regional uplift shortly before volcanism.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская